Collaborative Care Management for Depression - Kurt B. Angstman MS, MD; Ramona S. DeJesus MD; Mark D. Williams MD (SAGE Publishing, 2010)
The collaborative care management (CCM) model has been demonstrated to be significantly more effective compared to usual care (UC) in depression management although an initial increase in cost measures was seen. In this paper, cost measures as well as clinical response were analyzed on patients with available follow-up data at six months. Records of 219 patients with follow-up data in CCM group and 119 in UC group were reviewed. At six months, there was a statistically significant clinical response rate among patients in CCM compared to UC group ( P < 0.0001). Likewise, 65% in CCM group was "symptom-free" at 6 months vs. 31.9% in UC group ( P < 0.0001). Among the responders in both groups, there was no statistical difference in cost measures. However, cost measures were significantly higher among non-responders compared to responders within CCM. Between the two models, the non-responders in UC had lower cost measures than the non-responders under CCM.